Simultaneous quantification of emtricitabine and tenofovir nucleotides in peripheral blood mononuclear cells using weak anion-exchange liquid chromatography coupled with tandem mass spectrometry - Jansen, Robert S.; Rosing, Hilde; Kromdijk, Wiete; ter Heine, Rob; Schellens, Jan HM; Beijnen, Jos H. (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2010)
Emtricitabine (FTC) and tenofovir (TFV) are widely used antiviral agents that require intracellular phosphorylation to become active. This article describes the development and validation of an assay for the simultaneous quantification of FTC mono-, di- and triphosphate (FTC-MP, -DP and -TP), TFV and TFV mono- and diphosphate (TFV-MP and -DP) in peripheral blood mononuclear cells. Reference compounds and internal standards were obtained by thermal degradation of FTC-TP, TFV-DP, stable isotope-labeled TFV-DP and stable isotope-labeled cytosine triphosphate. Cells were lysed in methanol:water (70:30, v/v) and the extracted nucleotides were analyzed using weak anion-exchange chromatography coupled with tandem mass spectrometry. Calibration ranges in PBMC lysate from 0.727 to 36.4, 1.33 to 66.4 and 1.29 to 64.6 nM for FTC-MP, FTC-DP and FTC-TP and from 1.51 to 75.6, 1.54 to 77.2 and 2.54 to 127 nM for TFV, TFV-MP and TFV-DP, respectively, were validated. Accuracies were within −10.3 and 16.7% deviation at the lower limit of quantification at which the coefficients of variation were less than 18.2%. At the other tested levels accuracies were within −14.3 and 9.81% deviation and the coefficients of variation lower than 14.7%. The stability of the compounds was assessed under various analytically relevant conditions. The method was successfully applied to clinical samples.